PENGARUH KEMAJUAN TEKNOLOGI INFORMASI TERHADAP PERKEMBANGAN SISTEM INFORMASI AKUNTANSI - bagus Kusuma Ardi (LPPM STIE DHARMAPUTRA SEMARANG, 2013)
Advancement of Information Technology (IT) is growing very fast nowadays. This is a great influence to the development of Accounting Information Systems (AIS). In the development of Accounting Information Systems (AIS) through some turnover period ranging from accounting information systems based desktop until now has been developing accounting information systems development based website that can be accessed by intranet and internet.The rapid advancement of Information Technology (IT) is also the more advanced development of Accounting Information Systems, is evident from the data processing improvement, internal control, an increase in the amount and quality of information in financial reporting. The development of computer-based AIS in producing financial statements also affect the audit process. Finally, IT advances provide new opportunities for the accounting profession. New opportunities that may be achieved which are computer-based information systems consultant, CISA, and the audit of the trust web.Keywords: Information Technology (IT), Accounting Information Systems (AIS)